Authenticity, validation and sexualisation on Grindr: an analysis of trans women's accounts. Issue 1 (3rd April 2017) - Lloyd, Christopher E. M.; Finn, Mark D.
ABSTRACT: The socio-historic sexualisation of transgender identities is reported to have disaffirming consequences for the broad trans community, and for trans women in particular. Given trans people's increasing use of socio-sexual 'hook-up' apps, this paper looks at trans women's talk of self/other identifications in relation to their regular use of Grindr. Eight semi-structured in-depth interviews were conducted with London-based women who identified as trans* in some way. A Foucauldian-informed discourse analysis highlights intersecting frames of trans authenticity, validation and sexualisation. Within these frames, trans women can be variously positioned in gendered and sexualised ways. Specifically, a discourse of trans authenticity is seen to involve the marking out of an identificatory truth that is situated in culturally acceptable and hence de-sexualised womanhood, while a competing discourse of trans validation involves an ambiguity and eroticism that can serve to reimagine this truth. Trans subjectivities can thus consist of a desire for authentic (gendered and non-sexualised) selfhood, on the one hand, and self-affirming ambiguity and sexualisation on the other. That trans women can construct ambivalent relationships with trans-sexualisation discourse highlights the limitation of anti-sexualisation advocacy and implications for supporting trans sexualities are considered.